Enhanced Hysteresis Droop Control for Equivalent Load Sharing in Parallel PWM DC-DC Converters: Optimized Slew Rate by Resonant Filtering - Cagfer Yanarates; Aytac Altan (IEEE Access)
In this study, enhanced hysteresis droop control for equivalent and fast load sharing in parallel PWM DC-DC converters is presented. The basis behind the work encompasses power system stability, reliability, efficiency, reduction of losses and decrease in the operational cost. In this context, phase management, which constitutes the biggest problem, and the resulting factors such as ripple cancellation, thermal stress, transient response behavior and complexity, is aimed to manage with the proposed control scheme. Performance evaluation of the proposed system is based on sensitivity analysis against possible disturbance and noise, and comparative analysis with PI controller against uncertainty and parameter variations using mathematical modeling and simulation techniques. The results show that the proposed controller has improved performance in both noise attenuation and disturbance rejection at typical switching frequencies of DC-DC converters ranging from 100 kHz to a few MHz. Additionally, applying the proposed control technique considering 10% parameter variations led to the largest difference being recorded at 4% while this difference was 18.68% in conventional PI control. According to the findings of the simulation, the proposed control scheme reduces the settling time by a factor of 4.89, whereas it takes $775.862~μ $ s seconds with the PI controller. Furthermore, with the suggested controller, the overshoot—which was 36.09% with the PI controller—is reduced to just 1%.